Linkage study of voltage-gated potassium channels in familial mesial temporal lobe epilepsy - Cláudia Vianna Maurer‐Morelli; Rafael Breglio Marchesini; Rodrigo Secolin; Neide Ferreira dos Santos; Eliane Kobayashi; Fernando Cendes; Íscia Lopes‐Cendes (2007)
Voltage-gated potassium channels (VGKCs) play a critical role in the regulation of neuronal excitability and have been implicated in some types of epilepsies. Recently, autoimmune limbic encephalitis (LE) was associated with antibodies against VGKC. In addition, patients with LE showed partial epilepsy and increased T2 signal abnormalities in limbic structures. We have reported familial mesial temporal lobe epilepsy (FMTLE) associated with hippocampal atrophy (HA) and other signs of mesial temporal sclerosis detected by magnetic resonance imaging (MRI). In order to investigate whether VGKC may be associated to HA present in FMTLE, we perform linkage study in these candidate genes. Seventy-three microsatellites markers were genotyped in different human autosomal chromosome. Two-point LOD scores did not show evidence for linkage with any of the microsatellite markers genotyped (Zmax ranging from 0.11to-9.53 at theta=0.00). In the present study, linkage data showed no evidence that VGKC are involved in the determination of HA in FMTLE.